수소함유량에 따른 Zr-1.0Nb 합금 피복관의 기계적 물성치 변화 - 나연수; Yeon Soo Na; 최민영; Min Young Choi; 고대균; Dae Gyun Ko; 김윤호; Yoon Ho Kim; 목용균; Yong Kyoon Mok (대한금속·재료학회지, 54(3), 2016)
Hydrogen pre-charged Zr-1.0Nb alloy was prepared to study the effect of hydrogen uptake on its mechanical properties. The apparent activation energy of the Zr-1.0Nb alloy for hydriding was about 27 kcal/mol. The tensile strength of the Zr-1.0Nb alloy with a hydrogen content of up to 700 ppm was similar to that of an as-fabricated specimen, in that its elongation was drastically decreased after 400 ppm and became nearly zero above about 1200 ppm. The critical hydrogen content range needed to produce the ductile-brittle transition was above 400 ppm.